Pest species of a fungus gnat genus Bradysia Winnertz (Diptera: Sciaridae) injuring agricultural and forestry products in Japan, with a review on taxonomy of allied species. Issue 3 (30th July 2019) - Sueyoshi, Masahiro; Yoshimatsu, Shin‐Ichi
Abstract: Agricultural and forestry pest species of the Bradysia tilicola group from Japan were revised taxonomically after examination of the type specimens. A sciarid pest of Welsh onion occurred from northern Saitama, Japan since 2014 and later from south‐eastern Gunma, Japan, was identified as B. odoriphaga Yang & Zhang, 1985, sp. rev. It was removed from synonymy of B. cellarum Frey, 1948, being the first record of the species from Japan. Bradysia agrestis Sasakawa, 1978, was assigned to be a junior synonym of B. impatiens (Johannsen, 1912). Bradysia paupera Tuomikoski, 1960, sp. rev., was removed from synonymy of B. impatiens and was recognized as a distinct species. We also compiled their host plants and fungi hitherto reported from Japan. Bradysia impatiens was here recorded from an indoor facility of cloud ear fungus, Auricularia polytricha (Montagne) Sacc., for the first time. At least 19 cultural crops belonging to 12 plant and fungal families were reported as actual and potential hosts of B. impatiens . We suggested that B. impatiens and B. paupera might have been confused in studies of mushroom production in Japan. Further survey of distribution of B. paupera in Japan needs to be done. Abstract : Agricultural and forestry pest species of the Bradysia tilicola group from Japan were revised taxonomically after examination of the type specimens. Bradysia odoriphaga Yang & Zhang, 1985, sp. rev., was removed from a junior synonym of B. cellarum Frey, 1948, and was recorded from Japan for the first time. Bradysia agrestis Sasakawa, 1978, was assigned to be a junior synonym of B. impatiens (Johannsen, 1912).